Molecular organic materials : from molecules to crystalline solids - Fraxedas, Jordi (Cambridge : Cambridge University Press, 2006)
The interest in molecular organic materials is tremendous, driven by the need to find new materials with desirable properties. This book aims to bring the materials and surface science communities together, integrating physics and chemistry in a non-technical manner, ensuring this fascinating field can be understood by a multi disciplinary audience. Starting with basic physical concepts and synthetic techniques, the book describes how molecules assemble into highly ordered structures as single crystals and thin films, with examples of characterization, morphology and properties. Special emphasis is placed on the importance of surfaces and interfaces. The final chapter gives a personal view on future possibilities in the field. Written for beginners and experienced chemists, physicists and material scientists, this will be a useful introduction to the field of molecular organic materials.
An introduction to molecular organic materials -- Complex simplicity -- Building blocks: molecules -- Intermolecular interactions -- Crystal engineering: synthons -- Molecular organic materials -- Polymorphism -- Orbitals, bonds and bands -- Building molecules: molecular engineering -- Hexagons -- Pentagons -- Hexagons and pentagons -- Hexagons, pentagons and functions -- Really big molecules -- Building materials: crystal engineering -- Single crystals -- Thin films -- Patterning -- Interfaces -- Surfaces -- Organic/inorganic interfaces -- Organic/organic interfaces -- In situ characterization -- Thin-film growth: from 2D to 3D character -- Heterogeneous growth -- Dynamic scaling theory -- Control of orientation -- In situ studies of growth -- Nanometre-scale surface morphology -- Polymorphism -- A miscellany of physical properties -- 1D molecular metals -- 1D molecular magnets -- Interfacial doping -- Structure-property relationships -- Multiproperty materials.
Title from publisher's bibliographic system (viewed on 05 Oct 2015).
Keywords: Molecular structure; Organic compounds; Crystals